Dipthongs In Rejang Language - Auliansyah, Andri; Magria, Vera; Oktariza, Dodi (Krinok:Jurnal Linguistik Budaya, 2025)
This thesis analyses about Diphthongs in Rejang Language. The several points of this research are the classifications and formations of diphthongs in Rejang language. The purposes of this research to find out and explain diphthongs in Rejang language. The writer uses descriptive qualitative method to do the research. While, to analyze the data, the writer used theory from Peter Roach (1998) with supporting theory from Ramelan in Mustikareni (2013). The data are found by recorded the conversation of rejang native speakers. As the result, two classifications of diphthong by Roach (1998) were found, they are closing and centering diphthong. The writer found 19 diphthongs classified as closing diphthongs (eɪ/, /aɪ/, /aʊ/) and 8 diphthongs classified as centering diphthongs (/ɪә/, /eә/). The 27 diphthongs are the result from the data that the writer founds from the conversation in Rejang language.